Reproductive performance of female Nile tilapia Oreochromis niloticus L. in South Kivu (DR Congo): comparison of two strains differing in origin and history of domestication - F.J., Nihoreye,; U.N., Nyongombe,; L.G., Alunga,; B.D., Akonkwa,; M.P., Isumbisho,; O.F., Okitayela, (International Journal of Scientific Research and Management (IJSRM), 2019)
This study was conducted to evaluate the reproductive performance of females of Oreochromis niloticus originating from a strain of distant origin and extensively exploited in fish farming (Nyakabera strain) and a local strain recently removed from the natural environment (Lac Kivu strain). The experiment was carried out in triplicate with fry of 4.9 to 6.3 g placed in earthen ponds for a period of 6 months, at the Nyakabera fish station in South Kivu, Democratic Republic of Congo. The comparison of the two strains focused on the size of the first sexual maturity, gonado-somatic ratio, fecundity, egg diameter and condition factor. The results showed that under similar managed rearing conditions, the Nyakabera strain reaches sexual maturity earlier and is characterized by a higher gonado-somatic ratio and higher relative fertility, but a worse condition compared to the Lac Kivu strain. These differences, which indicate a better reproductive success of the Nyakabera strain, are related to the origin and the history of domestication, which are just as different from these two strains.